Aggregate Prevalence of Chemosensory and Sinonasal Dysfunction in SARS‐CoV‐2 and Related Coronaviruses. (19th May 2020) - Lehrich, Brandon M.; Goshtasbi, Khodayar; Raad, Richard A.; Ganti, Ashwin; Papagiannopoulos, Peter; Tajudeen, Bobby A.; Kuan, Edward C.
Abstract : Much of the published literature regarding the novel coronavirus disease 2019 (COVID‐19) constitutes lower respiratory system symptomatology, while there exists a paucity of data describing the complicated sequelae of the upper respiratory system, including chemosensory and/or sinonasal dysfunction. This study utilized the National Library of Medicine's PubMed/MEDLINE database to query for articles describing COVID‐19, SARS‐CoV‐2, SARS‐CoV‐1, MERS‐CoV, and other coronaviruses, with any mention of smell, taste, or other chemosensory or sinonasal dysfunction. Aggregate analysis demonstrated an incidence of 49.6% (n = 497 of 1002; 95% CI, 46.5%‐52.7%), 47.9% (n = 480 of 1002; 95% CI, 44.8%‐51.0%), and 17.9% (n = 880 of 4909; 95% CI, 16.9%‐19.0%) for smell loss, taste loss, and smell or taste loss, respectively, in patients infected with SARS‐CoV‐2. Additionally, there were significantly higher incidences of runny nose/rhinorrhea/rhinitis and nasal congestion/obstruction/blockage in other coronaviruses as compared with SARS‐CoV‐2 ( P <. 001). Understanding these less well‐characterized symptoms may help develop measures for estimating early markers of disease prevalence and/or resolution. Level of evidence: 4.